Biomechanical properties of the repaired and non-repaired rat supraspinatus tendon in the acute postoperative period. (4th May 2019) - Kurdziel, Michael D.; Davidson, Abigail; Ross, David; Seta, Joseph; Doshi, Shashin; Baker, Kevin C.; Maerz, Tristan
ABSTRACT: Purpose : The rat rotator cuff (RC) model is used to study RC pathology and potential treatment; however, native scar-mediated healing allows the rat RC to recover at 4–6 weeks but little is known about acute healing. This study characterized the properties of the repaired and non-repaired rat RC following surgical detachment.Materials and Methods : Forty-eight rats underwent surgical RC detachment and received surgical repair (Repair) or left unrepaired (Defect) to either 12 or 19 days. Healthy controls were obtained from contralateral limbs. Biomechanical properties were assessed using stress relaxation and failure testing and mechanical modeling performed using quasilinear viscoelastic (QLV) and structurally based elastic models. Histology and micro-magnetic resonance imaging were used to qualitatively grade tendon-to-bone healing.Results : Repair and Defect exhibited significantly inferior mechanical properties compared to Healthy at both time points. Repair had significant increases in peak, equilibrium, and ultimate stress, modulus, and stiffness and significant decreases in cross-sectional area, % relaxation, and QLV constant "C" between 12 and 19 days, whereas Defect showed no change.Conclusions : This study demonstrates acute differences in mechanical properties of the rat supraspinatus tendon in the presence and absence of surgical repair. Understanding the longitudinal recovery of mechanical properties can facilitate more accurate characterization of RC pathology or future treatments.